2005
DOI: 10.1039/b507263h
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotriphosphazene [N3P3(2,2′-dioxybiphenyl)2-(4-pyridinoxy)2] and its halogen bonded complex with 1,4-diiodotetrafluorobenzene

Abstract: We report the crystal structures of the title cyclotriphosphazene and its 1 : 1 molecular complex with 1,4-diiodotetrafluorobenzene. The latter crystal structure selectively includes CCl 4 molecules in bulbous cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The PO bonds that link the oxypyridine and biphenoxy units to the phosphazene skeleton are of normal length and are consistent with values reported for other related biphenoxy‐ or aryloxycyclotriphosphazenes 4a. 12, 32, 33, 34 All of the PN distances (average 1.579(2) Å), and the P‐N‐P (average 121.98(16)°) and N‐P‐N (average 118.29(14)°) angles lie within the expected ranges 35. Metalation does not cause any distortion in the cyclophosphazene ring skeleton.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The PO bonds that link the oxypyridine and biphenoxy units to the phosphazene skeleton are of normal length and are consistent with values reported for other related biphenoxy‐ or aryloxycyclotriphosphazenes 4a. 12, 32, 33, 34 All of the PN distances (average 1.579(2) Å), and the P‐N‐P (average 121.98(16)°) and N‐P‐N (average 118.29(14)°) angles lie within the expected ranges 35. Metalation does not cause any distortion in the cyclophosphazene ring skeleton.…”
Section: Resultssupporting
confidence: 84%
“…The previously reported crystal structure of the cyclotriphosphazene ligand I used in this work revealed an R,S configuration of the biphenyls around the phosphorus centers,32 the same as in the starting material gem ‐[N 3 P 3 (O 2 C 12 H 8 ) 2 Cl 2 ] 33. Variable‐temperature NMR spectroscopy studies were, however, not carried out, thus the occurrence of interconversion processes between stereoisomers of this cyclotriphosphazene at room temperature is still an open issue.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…[28] The electron-poor portion of the charge-transfer complex is generally an electron-deficient organic halide, and so 1,4-diiodotetrafluorobenzene has been used quite extensively. [12,15,16,18,24,29,30] Halogen bonding in which the halide is attached to a double or triple bond is known, but these systems have been the subject of much fewer studies. Polymeric chains result from the interaction between tetraiodoethylene (TIE) and diamines.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the stereochemistry was recorded for both racemic (170 [179] and 171 [196]) and meso (172 [196], 173 [197], 174 [198]) diastereoisomers, although for a number of structures the stereogenic properties were not recorded for either racemic (175 [199], 176 [200], 177 [201] ) or meso (178 [202], 179 [200]) compounds. The bis-BP motif is very common in metallocyclophosphazenes but the stereogenic properties were only stated in one study where the racemic form of bis-BP was observed (180 [203]).…”
Section: Derivatives Of Bis-bp Cyclotriphosphazenementioning
confidence: 99%